The Richness of Italian Historical Demography - Marco Breschi; Alessio Fornasin; Matteo Manfredini (Historical Life Course Studies)
In this paper, we present a new methodology for the reconstruction of individual life-histories based on information derived from the integration of different parish registers. This methodology makes it possible to associate the sequence and timing of demographic events not only with the structural features of the households in which they occurred, but also with more general historical context and the economic factors that shaped the lives of people and households. All these elements are then evaluated in a dynamic and temporal perspective, allowing the adoption of a longitudinal approach in the analysis of demographic processes for historical populations.